x2 -2016x +2015
Cho f(x)=x^2017-2016x^2016+2016x^2015-...+2016x-1. Tính f(2015)
Theo đề bài ta có
\(f\left(x\right)=x^{2017}-2016.x^{2016}+2016.x^{2015}-...+2016.x-1\)
Với \(f\left(2015\right)\)thì \(x=2015,x+1=2016\)
\(\Rightarrow f\left(x\right)=x^{2017}-\left(x+1\right).x^{2016}+\left(x+1\right).x^{2015}-...+\left(x+1\right).x-1\)
\(\Rightarrow f\left(x\right)=x^{2017}-x^{2017}-x^{2016}+x^{2016}+x^{2015}-...+x^2+x-1\)
\(\Rightarrow f\left(x\right)=x-1\)
\(\Rightarrow f\left(2015\right)=2015-1=2014\)
Vậy f(2015)=2014
\(x^{2017}-2016x^{2016}-2016x^{2015}-...-2016x^3-2016x^2-2016x\)
f(x)=x^2015-2016x^2014+2016x^2012+...-2016x^2+2016x-1
cho f(x)=x2017-2016x2016-2016x2015-...-2016x-1
Tính f(2015)
Tính giá trị của đa thức:
P(x) = x^{2017}-2016x^{2016}-2016x^{2015}-...--2016x^2^-2016x+1 tại x=2017
A(x)=x^21-2016x^20+2016x^19-2016x^18+...+2016x^3-2016^2+2016x-1
Tính gá trị đa thức A(x) tại x=2015
Cho đa thức :
A(x) = 2016- 2016x + 2016 x2 - 2016x3 + ... - 2016x2015 + x2016
Tính A(2015)?
Tính giá trị của đa thức:
P(x) = \(x^{2017}-2016x^{2016}-2016x^{2015}-...--2016x^2^-2016x+1\)
Cho P(x)=x^4-2016x^3+2016x^2-2016x+2016 Tính P(2015)
tính P(x) với x = 2015
P(x) = x17-2016x16+2016x15-2016x14+....+2016x-1